THE PROBLEM OF IMPROVING MUSICAL TRAINING OF A FUTURE TEACHER OF CHOREOGRAPHY - Khе Siuefej (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2016)
The research paper deals with the features of musical training of future teachers of choreography. It was found that the disciplines of basic as well as scientific and subject training, such as History of Music, Playing a Musical Instrument, Fundamentals of Music Theory, Analysis of Music in Choreography create conditions for quality musical training of future teachers of choreography. It was studied that the formation of emotional, conscious, action-and-practical attitude to music based on its perception and in the process of its implementation is through rational selection of organizational forms, methods, means and presentation of educational materials to support the cycle of basic as well as scientific and subject training using an electronic educational environment.